Hematological Response Studies of Climbing Perch (Anabas testudineus) Fed with Fermented Feed on the Fermentation of Kelakai Leaves (Stenochlaena palustris) - Fauzana, Noor Arida; Redha, El; Aminah (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze the nutritional value of fermented feed on kelakai leaves that are feasible as climbing perch feed and the hematological response of climbing perch raised by fermentation-based feeding of kelakai leaves. The study was carried out using an experimental method on the maintenance of climbing perch which was fed based on fermented leaves with 5 treatments and 3 tests. The parameters observed are the nutritional content of feed based on fermented leaves and hematological responses which include erythrocyte, leukocyte, hemoglobin, and hematocrit values. The results of the research on the nutritional content of feed showed that fermented feed on kelakai leaves has a protein content of 27%-31%, crude fiber content of 4%-7%, water content of 12%-14%, ash content of 11%-13%, fat content of 4%-6%. It was concluded that there was a decrease in fiber content and fat content and an increase in protein content, water content, and ash content. It happens gradually in line with the increase in probiotic dose. The results of the study on the hematological response of climbing perch are erythrocytes range from 1.65-3.91, leukocytes range from 223.23-287.43, hematocrit ranges from 15.30-35.07 and hemoglobin ranges from 5.37-10.33. The results of the proximate analysis of feed based on the fermentation of kelakai leaves showed that the values of water content, ash content, crude fiber, protein, and fat were in the recommended range. The hematological response of climbing perch shows good results and is in the normal range.